2007
DOI: 10.1186/1742-6413-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Sequential use of bronchial aspirates, biopsies and washings in the preoperative management of lung cancers

Abstract: BackgroundThe combination of cytology and biopsies improves the recognition and typing of small cell (SCLC) versus non small cell (NSCLC) lung cancers in the fiberoptic bronchoscopy assessment of centrally located tumours.MethodsWe studied whether bronchial aspirates performed before biopsies (BA) and washings performed after biopsies (BW) could increase the diagnostic yield of fiberoptic bronchoscopy. A series of 334 consecutive samples taken in patients with suspicious fiberoptic bronchoscopy findings was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The diagnostic yield of forceps biopsy in the present study was 80.5%, which was similar to the results of previous studies (3,6,16,18,23), and bronchial washing had a positive diagnosis rate of 37.8%. Most previous studies reported a similar positive diagnosis rate for cytologic analysis of bronchial washing (27%-49%) (3,5,15,18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The diagnostic yield of forceps biopsy in the present study was 80.5%, which was similar to the results of previous studies (3,6,16,18,23), and bronchial washing had a positive diagnosis rate of 37.8%. Most previous studies reported a similar positive diagnosis rate for cytologic analysis of bronchial washing (27%-49%) (3,5,15,18).…”
Section: Discussionsupporting
confidence: 91%
“…These patients accounted for 3.6% of all patients and 18.4% of bronchoscopic biopsy-negative patients. Previous studies have reported positive diagnosis rates of 2.1%-9.5% based on cytologic analysis only (3,4,7,15,23,27). Histologic type did not affect the positive diagnosis rate of washing cytologic analysis in these cases.…”
Section: Discussionmentioning
confidence: 42%
“…Similar results were reported by other studies which concluded that for endoscopically visible tumors, the diagnostic yield of BW does not differ whether performed before or after BB and biopsy. [228232233234] However, a prospective randomized trial by Hou et al . [235] concluded that in endobronchial exophytic tumors, prebiopsy brushing appears to be superior to postbiopsy brushing.…”
Section: Bronchoscopic Samplingmentioning
confidence: 99%
“…Similarly, Piaton et al . [232] concluded that the yield of fiberoptic bronchoscopy may reach close to 100% in the diagnosis and typing of centrally located, primary lung cancers by combining biopsies and pre–post-BW. These results have been supported by other studies as well.…”
Section: Bronchoscopic Samplingmentioning
confidence: 99%
“…Bronchial washing can be performed prior to or following biopsy sampling [38,39]. It is recommended that as much volume of washings as possible should be recovered after instilling 20-30 ml of isotonic saline [39,40].…”
Section: Exfoliative Cytologymentioning
confidence: 99%